Development and in-Vitro Evaluation of Liposomal Gel of Ciclopirox Olamine - ABHAY M. L. VERMA,; S.PALANI, (International Journal of Pharma and Bio Sciences, 2010)
The objective of the present study was to prepare liposomal gel bearing anti-fungal drug (Ciclopirox olamine) to provide controlled release of drug for topical treatment of patients with dermal infections and enhancing local effect. Different formulations of Liposomes were prepared by using thin film hydration method by varying the lipid phase composition (Phosphatidylcholine / cholesterol mass ratio) with drug. These prepared liposomes were characterized for their drug loading, encapsulation efficiency, morphological character, surface charge and size analysis as well as for transmission electron microscopy. Topical liposomal gels were prepared by incorporation of liposomes into different polymers (0.5% w/V Agar base, 0.5% w/V Carrageenan and 0.5% w/V Carrageenan/Agar in 1:1 Ratio) bases and their release characteristics were investigated.